Intercropping of Cereals with Lentil: A New Strategy for Producing High-Quality Animal and Human Food - Theodoros Gkalitsas; Fokion Papathanasiou; Theano Lazaridou (Agronomy)
Intercropping is an eco-friendly agricultural practice that can lead to increased productivity and improved resource efficiency. This two-year field study (2022–2023 and 2023–2024) aimed to evaluate the yield and quality (protein content) of lentil when intercropping with bread wheat (Yekora) and oat (Kassandra) under two spatial arrangements (1:1 alternate rows and mixed rows at a 50:50 seeding ratio) in northwestern Greece. A completely randomized design was applied with three replications. Differences were found between treatments regarding yield as well as protein content. Results showed that the highest total grain yield (2478.6 kg/ha) and land equivalent ratio (LER = 2.50) were recorded in the Yekora + Thessalia combination (alternate rows). Legume protein content remained consistently high (27–31%), while cereal protein content varied with genotype. Intercropping in alternate rows generally outperformed mixed sowing, indicating the importance of spatial arrangement in optimizing resource use. These findings suggest that properly designed cereal–lentil intercropping systems can enhance yield and quality while supporting sustainable agricultural practices. Intercropping of Yekora with lentil was superior compared to lentil and bread wheat monocultures and can be recommended as an alternative method for the production of human and animal food.